2019
DOI: 10.1007/s10875-019-00638-z
|View full text |Cite
|
Sign up to set email alerts
|

CAPS and NLRP3

Abstract: Cryopyrin associated periodic syndrome (CAPS) is a rare inherited autoinflammatory disorder characterized by systemic, cutaneous, musculoskeletal, and central nervous system inflammation. Gain-of-function mutations in NLRP3 in CAPS patients lead to activation of the cryopyrin inflammasome resulting in the inappropriate release of inflammatory cytokines including IL-1β and CAPS related inflammatory symptoms. Several mechanisms have been identified that are important for the normal regulation of the cryopyrin in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
150
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 192 publications
(160 citation statements)
references
References 82 publications
2
150
0
8
Order By: Relevance
“…CAPS are inherited autoinflammatory disorders characterized by systemic inflammation with fever often presenting with skin rashes and central nervous system inflammation. While arthralgia is common in patients with CAPS, arthritis is less frequent . Inflammation in CAPS is caused by gain‐of‐function mutations in NLRP3, leading to aberrant inflammasome activation and direct initiation of an inflammatory cascade .…”
Section: Nlrs Function As Sensors Of Pathogens and Cellular Perturbatmentioning
confidence: 99%
See 1 more Smart Citation
“…CAPS are inherited autoinflammatory disorders characterized by systemic inflammation with fever often presenting with skin rashes and central nervous system inflammation. While arthralgia is common in patients with CAPS, arthritis is less frequent . Inflammation in CAPS is caused by gain‐of‐function mutations in NLRP3, leading to aberrant inflammasome activation and direct initiation of an inflammatory cascade .…”
Section: Nlrs Function As Sensors Of Pathogens and Cellular Perturbatmentioning
confidence: 99%
“…While arthralgia is common in patients with CAPS, arthritis is less frequent. 19 Inflammation in CAPS is caused by gain-of-function mutations in NLRP3, leading to aberrant inflammasome activation and direct initiation of an inflammatory cascade. 20 These findings demonstrated that inflammasome activation per se was sufficient to initiate a full-blown systemic inflammation in humans.…”
Section: Nlr S Fun C Ti On a S S En Sor S Of Pathog En S And Cellulmentioning
confidence: 99%
“…These hereditary cryopyrin-associated periodic syndromes (CAPS) are typified by chronic inflammatory symptomology caused by point mutations in the NLR family gene NLRP3, resulting in the production of a hyper-active NLRP3 protein [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…NLR contains a pyrin domain such as NLRP3 and/or caspase activation domains (CARD), which promotes its self-assembly, some NLRs form multiprotein complexes called inflammasomes, which protect the cell from injuries as well as regulate homeostasis. The gain-of-function mutations in NLRP3 cause hyperactivation of cryopyrininflammasome and thus cause disease manifestations [31] [32].…”
Section: Cryopyrinopathymentioning
confidence: 99%